1112. Evaluating the Effects of Casirivimab-Imdevimab in Mild-to-Moderate COVID-19 Disease: A Matched Cohort Study. (15th December 2022) - Hage, Cindy; Martinez, Aileen; Dunham, Alexis; Mohseni, Nathan; Hernandez-Jimenez, Jarelys; Cardona, Lyssette L
Abstract: Background: In November 2020, the FDA issued an Emergency Use Authorization (EUA) for casirivimab-imdevimab (CAS-IMD) for the treatment of mild to moderate coronavirus disease 2019 (COVID-19) in certain high-risk patients. CAS-IMD is a monoclonal antibody cocktail that binds to COVID-19 spike protein receptor. Delta was the predominant strain in the US at the time. The purpose of this study is to evaluate if CAS-IMD administration to COVID-19 patients in the emergency department (ED) resulted in fewer hospitalizations and re-admissions. Methods: A retrospective chart review was conducted at Cleveland Clinic Martin Health which is composed of 3 hospitals and 1 free-standing ED. Patients with COVID-19 who met criteria for CAS-IMD in the ED from June 2021 to December 2021 were randomized into those who received CAS-IMD and those who did not. Patients were excluded if they had COVID-19 symptoms for >10 days or met EUA exclusion criteria for CAS-IMD. Cases and controls were matched by propensity score which was calculated by a logistic regression model including age, body mass index (BMI), sex, race and comorbidities. The primary outcome was the percentage of patients discharged from the ED who were hospitalized for COVID-19-related symptoms within 30 days. Secondary outcomes included number of CAS-IMD infusion-related reactions, ED return rate and subset analyses of severity of illness in the hospitalized. Statistical analyses were performed using two-sample t test or Wilcoxon rank sum test for continuous variables based on distribution, and Chi-square test or Fisher's exact test for categorical variables. Conditional logistic regression was used to compare the odds of hospitalization between groups. Results: Patients (N = 176) were matched 1:1 in each group. Eleven (12.5%) of the case group were hospitalized within 30 days of ED discharge vs. 36 (40.9%) in the control group. The odds of hospitalization in the CAS-IMD group were 81% lower than the control group (OR 0.19, 95% CI: 0.081-0.46, p< 0.001). After adjustment of covariates, the adjusted odds ratio remained significant (OR 0.12, 95% CI: 0.025-0.57, p=0.008). Conclusion: CAS-IMD use for mild-to-moderate COVID-19 infection in ED patients was associated with a lower incidence of hospitalization. Disclosures: All Authors : No reported disclosures.